2012
DOI: 10.4172/2155-6105.s7-001
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Oscillations in Alcoholism Research: A Review

Abstract: Alcohol dependence is characterized as a multi-factorial disorder caused by a complex interaction between genetic and environmental liabilities across development. A variety of neurocognitive deficits/dysfunctions involving impairments in different brain regions and/or neural circuitries have been associated with chronic alcoholism, as well as with a predisposition to develop alcoholism. Several neurobiological and neurobehavioral approaches and methods of analyses have been used to understand the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 211 publications
(211 reference statements)
0
10
0
Order By: Relevance
“…A history of adolescent extreme binge drinking was also associated with decreases in connectivity in all three cortical areas in response to sad facial expressions, as indexed by local phase locking. There have been a few studies that have evaluated ERO energy in specific frequency bands in individuals with alcohol-associated pathology (see [ 36 , 38 , 39 , 55 , 56 , 58 , 59 , 120 ]. In two sets of studies, it was demonstrated that both alcoholics [ 66 , 120 ] and young offspring of alcoholics at high risk for alcohol use disorders [ 67 ], show decreases in delta oscillations to target stimuli during a visual oddball task.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A history of adolescent extreme binge drinking was also associated with decreases in connectivity in all three cortical areas in response to sad facial expressions, as indexed by local phase locking. There have been a few studies that have evaluated ERO energy in specific frequency bands in individuals with alcohol-associated pathology (see [ 36 , 38 , 39 , 55 , 56 , 58 , 59 , 120 ]. In two sets of studies, it was demonstrated that both alcoholics [ 66 , 120 ] and young offspring of alcoholics at high risk for alcohol use disorders [ 67 ], show decreases in delta oscillations to target stimuli during a visual oddball task.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of underlying biomarkers of risk may be helpful in understanding the impact of adolescent extreme binge drinking and concomitant negative health behaviors. Electrophysiological variables represent some of the most reliable and sensitive biomarkers of vulnerability to—or endophenotypes for—alcohol-related psychopathology (for extensive reviews see: [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]). Reduced amplitude of the P300 or P3 component of the event-related potential (ERP) has perhaps received the most attention as a possible biomarker for AUD risk [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a behavioral level, these results are in line with the attentional deficits observed in BDs (Lannoy et al, 2017) and in AUD individuals (Maurage et al, 2014;Muller-Oehring and Schulte, 2014;Oscar-Berman and Marinković, 2007;Tedstone and Coyle, 2004), suggesting that impaired attentional control might contribute to alcohol-related problems. Indeed, it has been well established that alcoholics manifest reduced ERT power during cognitive tasks (Campanella et al, 2009;Kamarajan and Porjesz, 2015;Pandey et al, 2012;Porjesz et al, 2005;Rangaswamy and Porjesz, 2014).…”
Section: Discussionmentioning
confidence: 99%